The War Correspondent - Second Edition - McLaughlin, Greg (Pluto Press, 2016)
The War Correspondent looks at the role of the war reporter today: the attractions and the risks of the job; the challenge of objectivity and impartiality in the war zone; the danger that journalistic independence is being compromised by military control, censorship and public relations; as well as the commercial and technological pressures of an intensely concentrated, competitive news media environment. This new edition substantially updates the original, ending with an extended section on the return of history and ideology to the reporting of international conflict. It examines the "war on terror" framework that dominated the first decade of the 21st Century and, as Russia imposes itself once again on the international stage, asks if it might well give way to a new, Cold War framework. If so, what will that mean for the new generation of war correspondents, attuned not to history or ideology but the politics of the next conflict? The book features interviews with prominent war and foreign correspondents such as John Pilger, Robert Fisk, Mary Dejevsky and Alex Thomson.This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: Social Science / Media Studies; Social sciences; Electronic books